GX International quality healthcare for the Filipino - Corro, Philipp L. (School of Management, University of the Philippines Mindanao, 2006)
GX International, Inc. is in the business of improving and saving lives. In order to develop the quality of life and advance the well-being of the Filipinos, GX International, Inc. continues to seek for options so that quality treatment may not have to be expensive. This clearly exemplifies its business philosophy of providing quality yet inexpensive medicines to the Filipinos while yielding benefits for its stakeholders and employees. As the company prepares for expansions, numerous internal factors with a host of external conditions will certainly affect the firm's performance. With the advent of globalization and regionalization, competition among pharmaceutical companies will be tougher than ever. The "harmonization" scheme within the ASEAN region will mean more products and more players coming into the market. However, the GXI management team strongly believes that as long as competition exists, there is still room for expansion. Securing quality raw materials from other sources needs to be achieved in tandem with other considerations such as technological leadership, social acceptability, financial capability and overall organizational effectiveness. All these issues must be properly and successfully addressed to ensure the positive growth and expansion of the company. With this in mind, a strategic plan was prepared and developed to guide and direct GXI's management team in achieving the company's goal. The strategic management framework developed by Fred David was utilized in developing the plan, encompassing a comprehensive set of considerations including GXI?s internal and external environments, the strategic options available, and the control and improvement mechanisms needed.